A new species of Acanthodactylus Fitzinger, 1834 (Sauria: Lacertidae) from the Zagros Mountains, Iran - Mozaffari, Omid; Mohammadi, Sima; Saberi-Pirooz, Reihaneh; Ahmadzadeh, Faraham (Zootaxa, 2021)
Acanthodactylus boskianus is a widespread species in Northern Africa and Western Asia. In this study, we used morphological and genetic approaches to study populations of A. boskianus from the Zagros Mountains in western Iran, the easternmost limit of the species’ distribution. Our morphological and genetic data indicate that populations of A. boskianus in Iran are distinct from other populations of A. boskianus. Therefore, we describe the Iranian populations as Acanthodactylus zagrosicus sp. nov. The new species is the third endemic species of Acanthodactylus in Iran and the ninth Acanthodactylus species distributed in Iran overall. According to our surveys, this species is distributed widely in the Zagros Mountains including Kermanshah, Lorestan, Ilam, and Khuzestan Provinces.